Developing ICT Competency for Thai Teachers through Blended Training - Chaiya Akarawang; Pachoen Kidrakran; Prasart Nungchalerm (Journal of Education and Learning (EduLearn), 2016)
The purpose of this study aims to enhance teachers’ ICT competency. Three hundred and thirty seven teachers are surveyed through a questionnaire to identify training problems and training needs. Then the blended training model is implemented with teachers. The result showed that it can increase score in cognitive and attitude tests. The posttest score is higher than those pretest score at .01 level of statistical significance. Also, teachers’ ICT competency is in good level.